Treatment of Neuropathic Pain: Focus on Antidepressants, Opioids and Gabapentin - C Peter N Watson; Judith H Watt-Watson (Pain Research and Management)
BACKGROUND: The treatment of neuropathic pain continues to be difficult. Randomized, controlled trials (RCTs) provide some evidence to guide therapy. Most data relate to antidepressant therapy, although there is information on anticonvulsants and other treatments. Mistaken beliefs about many of these treatments are prevalent and need to be dispelled. Opioids are increasingly being used for the refractory patient. There has been recent enthusiasm for the anticonvulsant gabapentin for the treatment of these conditions.